Analisis Persepsi Siswa terhadap Penerapan Deep Learning dalam Pembelajaran di Sekolah Dasar - Artha Nurvia Fitri Rahayu; Mochammad Miftachul Huda; Ahmad Ipmawan Kharisma (Mataram University, 2026)
Current educational reforms have increasingly highlighted the importance of implementing deep learning to foster meaningful learning, higher-order thinking skills, and the ability to apply knowledge in authentic situations. Although numerous studies have investigated the effectiveness of deep learning in enhancing students’ learning outcomes, research examining students’ perceptions of its implementation, particularly in elementary education, remains limited. The novelty of this study lies in exploring students’ perceptions of deep learning implementation through four interconnected dimensions: cognitive, affective, social-collaborative, and reflective-applicative within the elementary school learning context. This study aimed to investigate students’ perceptions of the implementation of deep learning in classroom instruction at MIM 05 Tegalrejo. A descriptive qualitative approach was adopted, involving one Grade V teacher and Grade V and Grade VI students selected through purposive sampling. Data were gathered through classroom observations, semi-structured interviews, questionnaires, and documentation. The trustworthiness of the data was established using source, technique, and time triangulation, while data were analyzed through the processes of data reduction, data presentation, and conclusion drawing. The results showed that students generally held positive perceptions of the implementation of deep learning across the four dimensions examined. They demonstrated the ability to understand concepts, think logically, collaborate with peers, and relate classroom learning to real-life experiences. In addition, students exhibited strong learning motivation, active participation, reflective thinking, and a willingness to apply acquired knowledge in everyday contexts. Questionnaire findings further indicated that the cognitive, affective, social-collaborative, and reflective-applicative dimensions were predominantly rated within the good and very good categories. However, perceptions related to evaluation and assessment were relatively less favorable, with only 60% of students reporting satisfaction with the fairness of assessment, while 40% indicated that the feedback provided by teachers still required improvement. These findings suggest that deep learning has the potential to promote meaningful learning experiences in elementary education. Therefore, teachers are encouraged to enhance student-centered instructional practices, implement fair and transparent assessment procedures, and provide ongoing constructive feedback to maximize the effectiveness of deep learning in primary school classrooms.